Laser cladded Ni60WC coatings: Structure evolution, atomic model and electrochemical corrosion - Wang Jian; Jiang Yinfang; Wu Guoqing; Kong Dejun (Journal of Materials Research and Technology, 2025)
Laser cladded Ni60WC coating with superior corrosion resistance became promising for marine defense applications in marine environment, and the atomic-scale mechanisms governing their structure evolution and phase transition remained insufficiently understood. In this study, density functional theory (DFT) calculations were employed to analyze the phase stability, electronic structure and surface interactions of Ni60WC coatings, and the effects of laser power, laser scan speed and powder feeding speed on the electrochemical performance of obtained coatings in marine environment were investigated. The results show that all the coatings are composed of γ–Ni solid solution, WC, W2C and W3C phases, and the compositional redistribution is induced by the rapid solidification process, leading to the formation of metastable Ni–W–C phases. As the other laser cladding (LC) parameters are fixed, the lowest corrosion rates of Ni60WC coatings fabricated at the laser power (LP) of 2300 W, laser scanning speed (LSS) of 12 mm/s and powder feeding speed (PFS) of 16 g/min are 1.495 × 10−2, 2.366 × 10−2, and 2.868 × 10−2 mm/y, respectively, showing that the appropriate parameters are beneficial to enhancing the corrosion resistance, which is related with the influence of inherent phase transformation by the laser parameters. The findings contribute to the design of advanced Ni-based WC coatings for naval applications, improving their service life and structural integrity in harsh marine environments.